Iron- and copper-catalyzed Chemistry of iminoiodanes as novel synthetic strategies for C−N bond formation - Ton, Thi My Uyen (2013)
The work in this thesis was undertaken in Chemistry and Biological Chemistry, School of Physical and Mathematical Sciences in Nanyang Technological University from January 2009 to May 2012 under the supervision of Asst. Prof. Philip Wai Hong Chan. The work of this thesis has been directed toward the development of new iron and copper-catalyzed chemistry of nitrogen atom transfer reactions from iminoioddanes to C=C and C−H bonds as efficient synthetic strategies to C−N bond formation. This thesis is divided into three parts: Part I consists of Chapter I, which gives an introduction to iron and copper catalysis and its application to aziridination and amination of C=C and C−H bonds with hypervalent iodine(III) reagents. Part II is aimed at exploring novel nitrogen atom transfer reactions employing inexpensive, less-toxic and biocompatible nature of iron and copper catalysis. Chapter II details the efficient and practical iron-catalyzed synthetic route to acyl sulfonamides based on nitrene/imido insertion into the formylic C−H bond of aldehydes. The methodology is aimed to expand the reaction tolerance toward a structurally diverse set of starting aldehydes and compliment earlier works mediated by Ru(II) and Cu(I) catalysts. Detailed mechanistic studies to delineate this amination process will also be discussed. In chapter III, the intriguing conversion of 2-alkyl substituted 1,3-dicarbonyl compounds to α-acyl-β-amino acid and 2,2-diacyl aziridine derivatives mediated by Cu(OTf)2 and PhI=NTs are described. Complete control of product selectivity in the reaction is shown to be possible through slight modification of the reaction conditions. Chapter IV addresses a highly efficient copper-catalyzed amination of various 1,3-dicarbonyls compounds as a convenient and effective route to ketone substituted α-amino acid derivatives. Chapter V presents the ligand-free iron-catalyzed α-amination of saturated heterocyclic compounds via a nitrogen atom insertion to the α-C−H bond of the substrates. The synthetic utility of this methodology is exemplified by ring-opening of the α-aminated products by various nucleophiles to provide a range of substituted diamine and amino alcohol compounds. Part III contains experimental data (Chapter VI) and references (Chapter VII) pertaining to this thesis.